(3Gdbhd GdeMce aj eYQag cSha GdfjQ GdCYXes - (3QeVGf Hf UGdM Hf YeQ Hf MLGRqj GdSaWj GdNhGfcj,J (B1158 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3gPg QSGdg SejJgG Gdbhd GdeMce ai eYQag cSha GdfjQ GdCYXe LeYJgG ef CbhGd GdeJbOejf hQSGFd GdeJCNQjf eGTjG ajg Ydi CUhd GdQUO GdLOjO hGdCfehPL GdaQjO s
(3BNQgG (B:s
(3hjecf Cf jchf Hjf NSha hcSha fUa TgQ hgPG BNQ eG JjSQ s
(3GdfSNI HgG MhGTs
(3cKjQI GdedGMXGJ Ydi GdgGeTjfs
(3efbhdg ef fSNI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B32 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B172s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B359 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B82 s
Keywords: (3Gdadcs